2017
DOI: 10.1002/jcb.26086
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Carmustine and Selenite Inhibits EGFR Mediated Growth Signaling in Androgen‐Independent Prostate Cancer Cells

Abstract: Although aberrant androgen receptor (AR) signaling is a central mechanism for castration resistant prostate cancer (CRPC) progression, AR-independent growth signaling is also present in CRPC. The current therapeutic options for patients with CRPC are limited and new drugs are desperately needed to eliminate these crucial growth signaling pathways. We have previously shown that combination of carmustine and selenite effectively induces apoptosis and growth inhibition by targeting AR and AR-variants in CRPC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Prostate cancer is a heterogeneous disease in male reproductive system, which consists of androgen-dependent and androgen-independent varieties (22). Androgen deprivation therapy has achieved remarkable results in the treatment of advanced prostate cancer, and hormone therapy has gradually become an important method for the treatment of prostate cancer (23). For androgen-dependent prostate cancer, surgical castration therapy has a certain therapeutic effect (24).…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is a heterogeneous disease in male reproductive system, which consists of androgen-dependent and androgen-independent varieties (22). Androgen deprivation therapy has achieved remarkable results in the treatment of advanced prostate cancer, and hormone therapy has gradually become an important method for the treatment of prostate cancer (23). For androgen-dependent prostate cancer, surgical castration therapy has a certain therapeutic effect (24).…”
Section: Discussionmentioning
confidence: 99%
“…For example, treatment with JS-K, a glutathione S transferase-activated nitric oxide donor prodrug, for 24 h, increased the proportion of apoptotic cells, by inducing ROS production in prostate cancer cells (22RV1, C4-2, LNCaP, and PC-3) [ 140 ]. Interestingly, these authors also showed that the pro-apoptotic effect of JS-K is dose-dependent, and 22RV1 and C4-2 cells were more sensitive than LNCaP and PC-3 cells [ 141 ]. Furthermore, although selenite had a partial pro-apoptotic effect and carmustine showed no apoptosis induction in EGF-stimulated PC-3 cells, combination treatment with carmustine and selenite dramatically induced apoptosis in EGF-stimulated PC-3 cells [ 141 ].…”
Section: Apoptosis and Rosmentioning
confidence: 99%
“…Interestingly, these authors also showed that the pro-apoptotic effect of JS-K is dose-dependent, and 22RV1 and C4-2 cells were more sensitive than LNCaP and PC-3 cells [ 141 ]. Furthermore, although selenite had a partial pro-apoptotic effect and carmustine showed no apoptosis induction in EGF-stimulated PC-3 cells, combination treatment with carmustine and selenite dramatically induced apoptosis in EGF-stimulated PC-3 cells [ 141 ]. This combination treatment increased ROS production, which triggered apoptosis in 22RV1 and PC-3 cells [ 141 , 142 ].…”
Section: Apoptosis and Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, selenite can prevent nonenzymatic formation of parafibrin produced by the tumor cells, thus presenting them as “self” and entering the innate cellular immune system [13, 14]. Combined carmustine and selenite treatment significantly inhibited the transmission and proliferation of epidermal growth factor receptor signals and induced apoptosis in androgen-independent prostate cancer cells, suggesting their potential in castration-resistant prostate cancer therapy [15]. These observations indicating that SS reduced the weight of tumor xenografts are consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%